Implementation of Licensing Application Information System (SIAP) Policy at the Investment Office, One-Stop Integrated Services and Manpower of Bulukumba Regency - Murni, Hari Nur Cahya; Saifuddin, Andi Satria (West Science Law and Human Rights, 2024)
This research was conducted using a descriptive method with a qualitative approach in explaining the state of the object in describing the state of the object of research such as facts that occur in the field. Data collection techniques use interview, observation and documentation methods. While in data analysis techniques, researchers use triangulation techniques. Based on research conducted by researchers at the research site, it shows that the implementation of the licensing application information system in improving the quality of licensing services in Bulukumba Regency based on indicators is considered good but there are still obstacles that occur. The obstacles that occur are still a lack of understanding from the public regarding the SIAP application, inadequate human resources, inadequate facilities, Standard Operating Procedures are considered convoluted, networks and servers that often experience problems, and lack of media owned by the public to access SIAP services.